Recontextualizing Barstool Sports and Misogyny in Online US Sports Media. (August 2022) - Garcia, Christopher J.; Proffitt, Jennifer M.
This critical qualitative case study interrogates the roles Barstool Sports and its founder, Dave Portnoy, serve in reaffirming the narrative power of conservative cultural ideology in mainstream US sports media. Portnoy's targeted harassment of female journalists is analyzed as examples of how the outlet alienates critics of heteronormative, hypermasculine discourse within relevant cultural arenas in digital sports media. To examine how the company deflects criticisms of misogyny, we explore Barstool Chicks —an alternative version of the company's website targeting female audiences. Resultantly, Barstool and Portnoy undermine the potential for feminist-driven narratives in sports media and contribute to the normalization of repressive conditions within cultural industries that perpetuates the continued dominance of conservative ideology.